The effects of a two-year randomised controlled trial of whey protein supplementation on bone structure, IGF-I and urinary calcium excretion in older postmenopausal women. - Zhu, K.; Meng, X.; Kerr, Deborah; Devine, A.; Solah, Vicky; Binns, Colin; Prince, R. (American Society for Bone and Mineral Research, 2011)
The effects of dietary protein on bone structure and metabolism have been controversial with evidence for and against beneficial effects. Because no long-term randomised controlled studies have been performed, a two-year study of protein supplementation in 219 healthy ambulant women aged 70-80 years was undertaken. Participants were randomized to either a high protein drink containing 30g of whey protein (n=109) or a placebo drink identical in energy content, appearance and taste containing 2.1g protein (n=110). Both drinks provided 600 mg of calcium. DXA hip aBMD, 24h urinary calcium excretion and serum IGF-I were measured at baseline, one and two years. QCT hip volumetric BMD and a femoral neck engineering strength analysis were undertaken at baseline and two years. Baseline average protein intake was 1.1 g/kg body weight/day. There was a significant decrease in hip DXA aBMD and QCT vBMD over two years with no between group differences. Femoral neck strength was unchanged in either group over time. The 24h urinary calcium excretion increased significantly from baseline in both groups at one year but returned to baseline in the placebo group at two years at which time the protein group had a marginally higher value. Compared to placebo, the protein group had significantly higher serum IGF-I at one and two years (7.3-8.0%, P<0.05). Our study showed that in protein-replete healthy ambulant women, 30g of extra protein increased IGF-I but did not have beneficial or deleterious effects on bone mass or strength. The effect of protein supplementation in populations with low dietary protein intake requires urgent attention.